From mammary mystery to parasitic surprise: a rare case of primary breast hydatid cyst - Nazanin Zeinali Nezhad; Hamid Zeinali Nezhad; Amirhossein Shahpar; Aazam Gholami Shahrebabak; Maryam Gholami Shahrebabak; Faride Rashid Farokhi (BMC Infectious Diseases)
Abstract Background Primary breast hydatid cyst is an exceedingly rare manifestation of echinococcosis, with an incidence of less than 0.27% among all hydatid cyst cases. Case report This report presents a unique case of a 51-year-old multiparous female who initially presented with a painless left breast mass. Initial imaging studies, including ultrasonography and mammography, revealed a 4.5 × 4 cm cyst classified as BI-RADS 3. The cyst was initially managed with fine-needle aspiration and conservative treatment. However, it recurred twice over a six-month period, necessitating surgical excision. Preoperative laboratory work ups revealed eosinophilia, a finding initially overlooked but later recognized as significant. Histopathological examination of the excised specimen confirmed the diagnosis of a hydatid cyst. Post-surgical management included albendazole therapy, regular imaging follow-ups, and patient education on hygiene practices to prevent reinfection. Conclusion This case highlights the importance of considering parasitic etiologies in the differential diagnosis of breast masses, particularly in endemic regions. It also underscores the value of a multidisciplinary approach in managing such rare cases. The unexpected diagnosis of a primary breast hydatid cyst in this case serves as a reminder of the diverse presentations of echinococcosis and the need for heightened clinical suspicion in atypical breast lesions. Clinical trial number Not applicable.